Primulina qingyuanensis (Gesneriaceae), a new species from limestone areas in Guangdong, China - Ning, Zu-Lin; Wang, Jing; Smith, James F.; Kang, Ming (Phytotaxa, 2013)
A new species, Primulina qingyuanensis from Guangdong, China, is described and illustrated. It is similar to P. bicolor (W.T. Wang) Mich. Möller & A. Weber, but differs from P. bicolor by several morphological characters, both vegetative and reproductive.